Association of Organochlorine Pesticide Exposure as Endocrine Disruptors with Polycystic Ovarian Syndrome in North India - Ruchika Garg; Binita Goswami; Kamna Singh; Shaifali Singh; Prabhat Agrawal; Prashant Gupta; Urvashi Verma (Journal of Mid-Life Health, 2025)
Aim and Background: This study explores the correlation of blood levels of organochlorine pesticides (OCPs) between PCOS and non-PCOS women, considering the endocrine-disrupting properties of OCPs and their potential role in PCOS pathogenesis. Materials and Methods: A case–control study was conducted at Sarojini Naidu Medical College, Agra, from September 2022 to March 2024. Serum samples from 110 women diagnosed with PCOS and 110 age- and weight-matched controls were analyzed for 17°CP residues using gas chromatography. Clinical examination to calculate height, weight, body mass index, and waist–hip ratio was conducted. Signs of hyperandrogenism, such as acne and hirsutism, along with acanthosis nigricans, were documented. Hormonal profiles through chemiluminescence immunoassay were assessed. Correlation analysis entails examining connections between OCP and polycystic ovarian syndrome (PCOS) through the application of the Pearson correlation coefficient. Results: PCOS patients exhibited significantly higher levels of several OCPs, including Alpha BHC, Beta BHC, Gamma BHC, Delta BHC, Heptachlor, Heptachlor Epoxide, Endosulfan I, Endosulfan II, Endosulfan Sulfate, Aldrin, Endrin, Endrin Aldehyde, PP-DDE, PP-DDT, and PP-DDD (P < 0.05) in comparison to their age- and weight-matched controls. Dieldrin levels showed no significant difference in both cohorts. Elevated OCP levels correlated with increased androgens, insulin resistance, menstrual irregularities, and disrupted gonadotropin secretion in PCOS patients while no association was measured in controls. Conclusion: The findings suggest that environmental exposure to OCPs is associated with PCOS exacerbates the disease by disrupting hormonal balance and acting as endocrine disruptors. Further research is needed to confirm these associations and inform targeted interventions. Clinical Significance: This study highlights the potential role of OCPs in association with PCOS, emphasizing the need for public health measures to reduce exposure to these harmful chemicals, which may help manage PCOS symptoms and improve health outcomes for affected women.